ChemInform Abstract: Topochemical Mechanoactivated Phosphonylethynylation of Pyrroles with Chloroethynylphosphonates on Solid Al2O3 or K2CO3 Media. Issue 45 (November 2015) - Gotsko, Maxim D.; Sobenina, Lyubov' N.; Tomilin, Denis N.; Ushakov, Igor' A.; Dogadina, Albina V.; Trofimov, Boris A.
Abstract The phosphonylethynylation of pyrroles is achieved by grinding the substrates and Al2O3 intensively for 5 ‐ 10 minutes followed by standing of the reaction mixture under air.